2017
DOI: 10.1016/j.pan.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pancreaticoduodenectomy on endocrine and exocrine pancreatic function: A prospective cohort study based on pre- and postoperative function tests

Abstract: Although deterioration of endocrine function was expected after pancreatic resection, improvement is frequently observed in patients with newly diagnosed diabetes. Exocrine function deteriorates after pancreaticoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
6
0
3
Order By: Relevance
“…A Belgian prospective cohort study in patients who had to undergo PD for an oncological indication reported a PEI prevalence of 20% pre-operatively and 64.1% post-operatively. 30 Results from a not-yet published sub-analysis that took only pancreatic adenocarcinoma patients into account ( n = 159) showed a PEI prevalence of 26.6% before PD and 78.1% after PD. In the case of DP ( n = 39), the prevalence of PEI was 15% pre-operatively and 10% post-operatively.…”
Section: Prevalence Of Pei In Pcmentioning
confidence: 96%
“…A Belgian prospective cohort study in patients who had to undergo PD for an oncological indication reported a PEI prevalence of 20% pre-operatively and 64.1% post-operatively. 30 Results from a not-yet published sub-analysis that took only pancreatic adenocarcinoma patients into account ( n = 159) showed a PEI prevalence of 26.6% before PD and 78.1% after PD. In the case of DP ( n = 39), the prevalence of PEI was 15% pre-operatively and 10% post-operatively.…”
Section: Prevalence Of Pei In Pcmentioning
confidence: 96%
“…In 2017, Roeyen et al published a prospective study evaluating pancreatic function in 78 patients after pancreatoduodenectomy using the 13 C-labeled mixed-triglyceride breath test preoperatively and postoperatively. The results revealed that 64.1% of the patients required postoperative enzyme replacement therapy [29]. In another study, Lim et al observed exocrine and endocrine insufficiency in a prospective study with 227 patients who underwent pancreatic surgery.…”
Section: Pancreatic Resectionsmentioning
confidence: 97%
“…NOD has also been described in 15%-20% of patients[ 143 , 145 , 146 ] after surgery. One study reported deterioration of the glycaemic control in up to 40% post-operatively[ 147 ],when formal tests like OGTT and i.v. glucagon stimulation test were used.…”
Section: Effect Of Pc Treatment On Diabetesmentioning
confidence: 99%